The priming of visual picture cues on onomatopoeic processing of reduced-hearing students: An empirical study - Shuhua Su; Jinhe Han; Fuzhan Dong; Jianjun Chen (Acta Psychologica, 2025)
Onomatopoeia is the formation of a type of word that imitates its associated sound. Since onomatopoeic words involve sound, hearing-impaired students may have difficulty processing onomatopoeia. The purpose of this study was to examine whether visual cues can facilitate the processing of onomatopoeic words in hearing-impaired students. Thirty-eight typically-hearing students (students without hearing impairments) and 40 hearing-impaired students from China participated in this study. The 40 hearing-impaired students included 20 with hearing aids and 20 with cochlear implants. Two different experiments were conducted. One examined the influence of cartoon pictures on the processing of onomatopoeic words in hearing-impaired students and the other examined the influence of images (photorealistic image that tend to resemble photographs; not cartoon pictures) on the processing of onomatopoeic words in hearing-impaired students. Our results revealed that in both experiments, the accuracy of the consistent level was significantly higher than that of the inconsistent level and the response time of the consistent level was markedly shorter than that of the inconsistent level. The accuracy of hearing-impaired students was significantly lower than that of typically-hearing students. Experiment 2 rendered similar results except for the accuracy of hearing-impaired students were higher than that of typically-hearing students, and their response time was shorter than that of hearing students. Our findings revealed that cartoon pictures as cue can improve the speed of onomatopoeic processing, which may be related to the characteristics of cartoon pictures. This study provides implications that may promote further study and experimentation regarding how hearing-impaired students develop language.